Adsorption behavior modeling of confined hydrocarbons in shale heterogeneous nanopores by the potential theory. Issue 10 (8th June 2022) - Dong, Xiaohu; Luo, Qilan; Wang, Jing; Liu, Huiqing; Chen, Zhangxin; Xu, Jinze
Abstract: In this article, a new method is proposed to quantificationally evaluate the effect of pore heterogeneity on the adsorption behavior of fluids in nanopores. First, the assumptions of furrowed, sinusoidal, and ravine pore surfaces are proposed to represent the heterogeneous nanopores in shale. Under the assumptions, a multicomponent potential theory of adsorption (MPTA) is coupled with Peng–Robinson equation of state (PR EOS) to model the adsorption behavior of hydrocarbons in nanopores. And, the geometrical and chemical heterogeneities in shale nanopores are, respectively, simulated by a spatial alteration and an amplitude deformation on potential energy. The fluid–fluid interaction is modeled by PR EOS, and the fluid‐pore wall surface interaction is simulated by a Steel 10‐4‐3 model for slit‐like nanopores and by a modified Lennard–Jones (LJ) 12‐6 model for cylindrical ones. Thereafter, the results of our theory are compared against the experimental data of shale rocks to validate its accuracy.